Curse of the night witch eaudiobook - Aster, Alex (Emblem Island, 2020)
A fast-paced series starter perfect for fans of Aru Shah and the End of Time and filled with adventure, mythology, and an unforgettable trio of friends. On Emblem Island all are born knowing their fate. Their lifelines show the course of their life and an emblem dictates how they will spend it. Twelve-year-old Tor Luna was born with a leadership emblem, just like his mother. But he hates his mark and is determined to choose a different path for himself. So, on the annual New Year's Eve celebration, where Emblemites throw their wishes into a bonfire in the hopes of having them granted, Tor wishes for a different power. The next morning Tor wakes up to discover a new marking on his skin...the symbol of a curse that has shortened his lifeline, giving him only a week before an untimely death. There is only one way to break the curse, and it requires a trip to the notorious Night Witch. With only his village's terrifying, ancient stories as a guide, and his two friends Engle and Melda by his side, Tor must travel across unpredictable Emblem Island, filled with wicked creatures he only knows through myths, in a race against his dwindling lifeline.